PHARMACODYNAMIC MECHANISMS FOR DEVELOPMENT OF TOLERANCE TO ACTION OF ANTICONVULSANT DRUGS - Мовчан, О.Д. (World of Medicine and Biology, 2015)
The development of the tolerance to the anticonvulsant drugs is one of essential problems of epilepsy treatment. In this regard, the question arises concerning the development of the approaches to eliminate the tolerance to anticonvulsants. However, it is possible to solve this problem only on a theoretical basis of determination of the principles and mechanisms of the development of tolerance to the different anticonvulsant drugs.The aim of the research was to determine the functional state of the neurotransmitter systems using selective agonists and antagonists of different types of receptors. Materials and methods. Experiments were conducted on the nonlinear white mice, males and females, weighing 18-20 g. The study anticonvulsants included phenobarbital, 20 mg/kg, carbamazepine, 125 mg/kg, depakine, 155 mg/kg. Experimental seizures were modeled using intraperitoneal administration of the chemoconvulsants. GABA receptor antagonists include picrotoxin (6 mg/kg) and corazol (100 mg/kg), bikukulline (20 mg/kg), and the GABA synthesis inhibitor thiosemicarbazide (20 mg/kg). They were used to analyze the GABA-ergic system. The role of the glycinergic system and glutamatergic system were performed using glycine receptor antagonist strychnine (1.5 mg/kg) and glutamate receptor agonist kainic acid (30 mg/kg).ResultsSignificant changes in functioning of the GABA-ergic neurotransmitter system of the brain are observed under the development of tolerance to the anticonvulsant action of phenobarbital. No another brake glycinergic and the excitatory glutamatergic systems were involved in the mechanisms of tolerance to anticonvulsant action of phenobarbital.It was shown that the GABA-ergic mechanism take part in the development of tolerance to carbamazepine. Probably glycinergic component in the mechanism of action of carbamazepine do not play a essential role in the development of tolerance to that drug. Тhе GABA-ergic system is also involved in the formation of tolerance to the anticonvulsant action of depakine.ConclusionsThe part of the GABA-, glycine- and glutamatergic systems of the brain in the mechanisms of action of anticonvulsant drugs was investigated. It has been shown that the effect of anticonvulsant drugs phenobarbital, carbamazepine, depakine offset in tolerant animals in the model corazol, picrotoxin, bicuculline and thiosemicarbazide convulsions.No differences in functioning of the glycine- and glutamatergic systems have been found between intolerant animals and animals tolerant to the action of phenobarbital and carbamazepine.
Keywords: anticonvulsant drugs; tolerance; GABA-; glycine- and glutamatergic systems